Media learning of dongle during covid-19 pandemic - Alfitriani Siregar; Imelda Darmayanti Manurung (PROCEEDING UMSURABAYA, 2020)
Abstract. The objective of study was to analyse the application of learning media throughthe dongle during Covid-19 pandemic this year. This research method conductedqualitative. Population were all fourth semester students of English Language Education, Faculty of Teacher Training and Education in the even semester of the 2019/2020 years, with a total population of 136 students. Sample were 32 students 4th semester of the English education. The development of science and technology shifts the paradigm of conventional learning towards innovative learning models. Now, students need learning media using dongles in the class that can ease learning by carrying out activities systematically, where they have to explain, presentation, find references easily. They have not been able to properly use a smartphone that actually affects their learning motivation. In fact, the presentation of student assignments through the dongle will likely be highly innovative. It is the learning media that functions to direct students to obtain a variety of learning experiences during covid-19 pandemic that are determined by student interactionwith the media. Making it easier for them to apply learning media by using a smart phone through the dongle